Corpus-Assisted Analysis of Robert Frost’s Poem, “Into My Own” Using AntConc - Amira, Hasan Saad; Monaliza, Sarbini ((UPSI Press), Universiti Pendidikan Sultan Idris, 2022)
This study aims to analyse the lexical features of one of Robert Frost’s poems, ‘Into My Own’ using Laurence Anthony’s AntConc. Based on a qualitative approach, the descriptive method was used to examine the information retrieved from the quantitative analysis of the literary text. The keyword method is to find out the most frequent words. Results show that corpus-assisted quantification of linguistic phenomena reveal more evidence than past studies which were intuitively analysed. Therefore, the findings indicate that using computer toolkits to analyse literary texts, mainly poems is possible by investigating lexical features to enhance themes, in this particular poem, the theme is a journey of independence. This study shows that the selection of only lexical features may seem insufficient but, eventually it is not possible to study all the poem’s linguistic features.